Revealing the Design Principles of Ni‐Rich Cathodes for All‐Solid‐State Batteries. Issue 13 (23rd February 2022) - Jiang, Wei; Zhu, Xinxin; Huang, Renzhi; Zhao, Shu; Fan, Xinming; Ling, Min; Liang, Chengdu; Wang, Liguang
Abstract: Electrode microstructure is one of the primary factors determining the electrochemical properties of all‐solid‐state batteries (ASSBs). However, the key principles of electrode design to realize fast ionic/electronic transport pathways are not well elucidated. Herein, the correlation between electrode microstructure and electrochemical behaviors is studied through different electrode design in terms of energy‐density‐related electrode composition and Ni‐rich layered oxides particle size distribution. A positive relation between particle size and mass fraction in electrode design is revealed, that is, as the particle size increases, more cathode materials are required to enable the fast reaction kinetics. The well interconnected active particles and solid electrolytes construct the highly percolated ionic/electronic transfer networks, which determines the overall electrochemical properties. The findings in this work give a new insight into electrode design to promote the development of high‐energy and high‐power ASSBs. Abstract : A positive correlation is revealed between particle size distribution and mass fraction of cathode materials in electrode design of Ni‐rich cathodes for all‐solid‐state batteries. As the particle size increases, more cathode materials are required to build the fast ionic/electronic transfer pathways for enabling the best rate capability.